2014
DOI: 10.3109/10826084.2014.903751
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Cardiovascular Effects from the Use of Anabolic-Androgenic Steroids as Ergogenic Resources

Abstract: This review evaluates the documented cardiovascular functioning among anabolic-androgenic steroid (AAS) users. AAS users manifest a reduction in HDL cholesterol, increased inflammatory markers, and oxidative stress. Strong evidence associating AAS use with blood pressure at hypertensive levels, as well as hypertrophy and cardiac dysfunction has also been reported. Both epidemiological and autopsy studies attest the relationship between AAS use and early mortality. The review's limitations are noted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 45 publications
3
22
0
Order By: Relevance
“…10 Moreover, the use of anabolic steroids is associated to a significant increase in blood pressure values; 11 this phenomenon is probably related to the sensivity of endothelium to catecolamine levels, to the renin and aldosteron production, or to others pathways. 12 Data from a follow-up study, as reported by Pereira dos Santos et al, showed that these effects appeared to be relatively short lived; 13 currently there is a lack in evidence on the use of steroids in the longer term. A recent study reported the association between recreational of anabolic steroid use and arterial hypertension and hyperlipidemia; 14 Severo et al reported that changes in lipid profile, were associated to an increase in inflammatory markers and endothelial dysfunction.…”
Section: Resultsmentioning
confidence: 99%
“…10 Moreover, the use of anabolic steroids is associated to a significant increase in blood pressure values; 11 this phenomenon is probably related to the sensivity of endothelium to catecolamine levels, to the renin and aldosteron production, or to others pathways. 12 Data from a follow-up study, as reported by Pereira dos Santos et al, showed that these effects appeared to be relatively short lived; 13 currently there is a lack in evidence on the use of steroids in the longer term. A recent study reported the association between recreational of anabolic steroid use and arterial hypertension and hyperlipidemia; 14 Severo et al reported that changes in lipid profile, were associated to an increase in inflammatory markers and endothelial dysfunction.…”
Section: Resultsmentioning
confidence: 99%
“…To date, there are no documented cases of primary PTH in an AAS user however the adverse cardiovascular effects of misuse that might be implicated in this case are known 3. There is strong evidence associating AAS use with hypertension and cardiac dysfunction 3.…”
Section: Discussionmentioning
confidence: 95%
“…There is strong evidence associating AAS use with hypertension and cardiac dysfunction 3. With each of the three returns to theatre with acute PB at least one systolic spike in blood pressure was noted.…”
Section: Discussionmentioning
confidence: 98%
“…Importantly, the bodybuilding practitioner had reduced HDL levels throughout the AAS self-administration, in addition to the increased TG levels. These results are alarming, as cardiovascular risk is expected to increase in individuals with low levels of HDL [ 8 9 10 ]. Thus, this case report serves to highlight the harmful effect of AAS misuse on lipoprotein metabolism related to cardiovascular risk.…”
Section: Discussionmentioning
confidence: 99%